NATURAL ECOTOURISM DEVELOPMENT IN THE KRUENG GEUNIE LHOK KEUTAPANG AREA, PIDIE REGENCY - Diah Ramadhani; Rahmawaty Rahmawaty; Ternala A. Barus (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
Objects and tourist attractions are one of the important elements in the world of tourism. Where objects and tourist attractions can succeed the government's program in preserving the nation's customs and culture as assets that can be sold to tourists and can improve welfare and community participation in preserving the development of a tourist area. The purpose of this study was to determine the priority factors in the development of ecotourism in the Krueng Geunie area. The benefits of this research are as a support and evaluation material for environmental-based tourism development and can create cooperation between the government and the private sector or managers in developing ecotourism in Pidie Regency. Data collection methods were carried out by means of observation, interviews with expert respondents, document studies and conducting Focus Group Discussions (FGD). The method used in this research is the Analytical Hierarchy Process (AHP) and the data is processed using expert choice software. Based on the results of the study, the weight structure of Krueng Geunie's natural ecotourism development criteria is in the first place, namely the socio-economic aspect criteria with a weighted value of 0.308. Then for the weight of the destination sub-criteria, the first rank is the tourism-aware group sub-criteria with a weighted value of 0.684. Furthermore, the weight of the alternative criteria in the first place is the development of the capacity of community elements with a weight value of 0.373.